PEMANFAATAN PERKEBUNAN KARET PADA PT. PERKEBUNAN NUSANTARA IX OLEH MASYARAKAT BATANG TAHUN 1993-2003 - Anggriyanto, Pradipta (Journal of Indonesian History, 2014)
Indonesia is the country with the largest rubber plantation in the world, although the new rubber plant was introduced in 1864 which at that time was still a Dutch colony. Indonesian rubber plantation companies inseparable from periods of Indonesian peoples resistance in an attempt to gain independence from Dutch colonial rule. PT. Nusantara Plantation Trunk IX is one of the company resulting from the nationalization of a colonial plantation. The purpose of this study was to determine the development of rubber plantations, plantation management cooperation between peoples with PT. IX Nusantara Plantation Trunk years 1993-2003.Â  The analysis was conducted using qualitative analysis interaktif.Lokasi research is PT. Plantation Nusantara IX Batang, Central Java. The results of this research indicate that PT. Nusantara Plantation Trunk IX has become a field of income for the local community, as was first made by the Dutch people have to use them in a way to work in the rubber plantations around. In 1993 occurred just after forest replanting of old Dutch colonial era and cut down on the time it was also a lot of people who work in PT. Plantation Nusantara IX, many people who use them by means of intercropping and was carried from generation to generation until now. Between the years 1993-2003 after the execution of the new rubber replanting workers is increasing with the number of plants that have been actively put gum in particular after 6 to 7 years of planting. Â